2000
DOI: 10.1177/001440290006600209
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Service Trajectories of Students with Disabilities Recommended for Expulsion from School

Abstract: Forty-one students who had special education histories and who were recommended for expulsion in one district were grouped and described according to their disability, onset of services, and services trajectory. Most students exhibited additional emotional and behavioral risk factors or were experiencing stressful family circumstances. The age at which special education services were initiated was related to case complexity and possible confusion about how best to serve the student within the context of specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…found that students with disabilities were over-represented in school expulsions. These authors also found that within a sample of students with disabilities who had been recommended for expulsion, there were varied patterns of development of these disabilities, paralleled by difficulties in home, school, and community settings (Morrison & D'Incau, 2000).…”
Section: Student Behavioral Characteristics Discipline and The Predmentioning
confidence: 93%
See 1 more Smart Citation
“…found that students with disabilities were over-represented in school expulsions. These authors also found that within a sample of students with disabilities who had been recommended for expulsion, there were varied patterns of development of these disabilities, paralleled by difficulties in home, school, and community settings (Morrison & D'Incau, 2000).…”
Section: Student Behavioral Characteristics Discipline and The Predmentioning
confidence: 93%
“…First, the possibility of this prediction assumes that there is causal homogeneity, that some subset of variables measured for all participants will account for a significant proportion of variance in a multivariate statistical model (Hoagwood, 2000). This assumption is repeatedly challenged by research literature that suggests that there are multiple subtypes and a variety of developmental trajectories that describe this population (Loeber, 1996;Morrison & D'Incau, 2000). Most research has focused on markers or correlates, not on the developmental or causal processes through which antisocial behavior develops across time (Hoagwood, 2000).…”
Section: Student Behavioral Characteristics Discipline and The Predmentioning
confidence: 99%
“…The Early Warning, Timely Response document (U.S. Department of Education, 1998) highlighted a number of characteristics of students who are likely to engage in antisocial behavior, including feelings of rejection, low school interest, poor academic performance, and impulsive behavior. Recent studies about school expulsions as disciplinary mechanisms have suggested that students who violate school norms and rules often have complex schooling histories and unidentified emotional and behavioral disabilities (Morrison & D'Incau, 1997, 2000. These findings emphasize the importance of early identification of students who are likely to exhibit antisocial behavior at school.…”
mentioning
confidence: 99%
“…Assessments conducted by school psychologists are often static measures of competence that may fail to provide a developmental or historical perspective on a child's performance in school. For example, in their study of students with special education needs who also were involved in school discipline processes, Morrison and D'Incau (2000) found that behavioral outbursts or rule-breaking offenses were rarely a complete surprise to school officials. Examination of student cumulative files for these special education students, which Keogh, Kukic, Becker, McLoughlin, and Kukic (1975) referred to as chronicles of disaster, revealed that the developmental trajectories for these students were a complex interweaving of student characteristics and educational events.…”
Section: Constructing An Organizing Rubric For Understanding Student mentioning
confidence: 99%